Xylanases and its Application in Food Industry: A Review - C. Ramalingam, Annie Deborah Harris and (Journal of Experimental Sciences, 2010)
<div style="border-bottom: medium none; border-left: medium none; padding-bottom: 0in; padding-left: 0in; padding-right: 0in; background: white; border-top: windowtext 1pt solid; border-right: medium none; padding-top: 1pt; mso-element: para-border-div; mso-border-top-alt: solid windowtext .5pt;"> Xylan is the most abundant and prinicipal type of hemicellulose. It is a linear polymer of β-D xylopyranosyl units linked by (1–4) glycosidic bonds. Xylanases are most predominantly present in plant cell walls and are produced by different kinds of microorganisms like bacteria, fungi, protozoans and some yeast. Recently there is an increasing demand for cost effective microbial xylanolytic enzyme which benefits the industrial applications and are produced commercially. Xylanases has a wide range of applications in pulp and paper, food, animal feed, textiles and pharmaceuticals. This review discusses some of the properties of xylanases and their application in food industry.